Screening for depressive and/or anxiety disorder in pharmacy course students at a Brazilian public university (Research, Society and Development, 2021)
The study aimed to estimate the prevalence of positive screening for depressive and anxiety disorders in undergraduate pharmacy students at a public university in the state of Paraíba. Validated questionnaires for screening for depression (PHQ9) and anxiety (BAI) were administered to undergraduate pharmacy students enrolled at the university. Students over 18 years old, with no previous diagnosis of mental disorders, participated in the research. The research was submitted to the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraíba, being approved under Opinion No. CAAE 15399019.4.0000.5188. The results showed that 34% of the evaluated students had scores compatible with moderate to severe depression and 18% with scores compatible with moderate to severe anxiety. A positive Pearson correlation (r = 0.672) was observed about the scores of the questionnaire for depressive and anxiety disorders. A positive correlation was identified between age and PHQ9 scores (r= 0.059). There was no correlation between age and BAI scores, as well as between the PHQ-9 (r= 0.003) or BAI (r= 0.033) scale score in correlation with the students' income. The data show that there is a high prevalence of possible mental disorders in pharmacy students at UFPB, with the care and intervention of the pharmacist being essential for proper monitoring and treatment, to promote an improvement in the quality of life of university students.